Structural Characterization of Mucin O-Glycosylation May Provide Important Information to Help Prevent Colorectal Tumor Recurrence - Mihalache, Adriana; Delplanque, Jean-François; Ringot-Destrez, Bélinda; Wavelet, Cindy; Gosset, Pierre; Nunes, Bertrand; Groux-Degroote, Sophie; Léonard, Renaud; Robbe-Masselot, Catherine (Frontiers in Oncology, 2015)
Although colorectal cancer is a preventable and curable disease if early stage tumors are removed, it still represents the second cause of cancer-related death worldwide. Surgical resection is the only curative treatment but once operated the patient is either subjected to adjuvant chemotherapy or not, depending on the invasiveness of the cancer and risks of recurrence. In this context, we investigated, by mass spectrometry (MS), alterations in the repertoire of glycosylation of mucins from colorectal tumors of various stages, grades, and recurrence status. Tumors were also compared with their counterparts in resection margins from the same patients and with healthy controls. The obtained data showed an important decrease in the level of expression of sialylated core 3-based O-glycans in tumors correlated with an increase in sialylated core 1 structures. No correlation was established between stages of the tumor samples and mucin O-glycosylation. However, with the notable exception of sialyl Tn antigens, tumors with recurrence presented a milder alteration of glycosylation profile than tumors without recurrence. These results suggest that mucin O-glycans from tumors with recurrence might mimic a healthier physiological situation, hence deceiving the immune defense system.